Breast Care for Pregnant Women and Postpartum Mothers - Ayu Devita Citra Dewi; Susmita (Jurnal Pengabdian Masyarakat Formosa, 2022)
Breast care is very important to expedite the process of removing milk. The benefits of breast care are to maintain cleanliness, especially on the nipples, prevent various diseases, strengthen the nipples, stimulate the milk glands in the breast so that milk production is more abundant and smooth, detect any abnormalities in the breast. milk dams, mastitis, and breast abscess. This shows that breast care is very important for the breastfeeding process (Rosyati, 2016). Implementation of activities is carried out with health promotion in the form of counseling to pregnant women and postpartum women or postpartum mothers at the Multiwahan Health Center. Counseling participants were pregnant women who checked their pregnancies and postpartum mothers who checked themselves or mothers who brought their babies for immunization to the Multivehicle Health Center then were collected in the waiting room and then given counseling about breast care by distributing leaflets and explaining counseling materials, and demonstrating how to do breast care using a breast phantom the participants listen, pay attention to the counseling material then do a debriefing.